Design of cylindrical soft vacuum actuator for soft robots. (12th March 2021) - Cheng, Peilin; Ye, Yuze; Jia, Jiangming; Wu, Chuanyu; Xie, Qizhi
Abstract: Soft robots have been significantly studied in recent decades, and among their key components are soft actuators. Vacuum is one of the main drivers of soft actuators. In this study, we propose a novel cylindrical soft vacuum actuator (CSVA) consisting of a top layer, bottom layer, and cylindrical internal chamber. Under a vacuum, the bottom layer was concaved into the internal chamber. A simplified analytical model was established to analyze the relationship between the vacuum pressure and the deformation height of the bottom layer. A validation experiment was conducted to verify the effectiveness of the proposed analytical model. The potential applications of the CSVA in the design of soft robots were also explored. A jellyfish-inspired swimming robot, an octopus-inspired suction cup, and a soft–rigid gripper were designed according to the concave deformation of the bottom layer. Then, the swimming speed of the swimming robot, the adsorption force of the suction cup, and the grasping capability of the soft–rigid gripper were investigated. The experimental results show that the maximum swimming speed of the swimming robot is 55.3 mm s −1 at a flapping frequency of 0.6 Hz. The adsorption forces of the suction cup both in air and underwater are 16.8 N and 17.5 N, respectively. The soft–rigid gripper with a pinching-grasping mode can grasp objects of various shapes and sizes in air and underwater. The experimental results demonstrate the feasibility of the soft vacuum actuator in the design of various soft robots.